Effect of A Probiotic Preparation on Gut Microbiota in Critically Ill Septic Patients Admitted to Intensive Care Unit: A Pilot Randomized Controlled Trial - Ata Mahmoodpoor; Roya Ghaemi; Kamran Shadvar; Seied-Hadi Saghaleini; Sama Rahnemayan; Ali Shamekh; Sarvin Sanaie (Tabriz University of Medical Sciences, 2023)
Background: Sepsis promotes severe physiologic alterations in patients, and it has been reported to induce profound changes in the gut microbial composition. The decrease of 'health‑benefiting' microbes and the increase in dysbiosis in critically ill patients are thought to induce or aggravate sepsis. In this study, we aimed to explore the effect of a probiotic preparation, Lactocare®, on gut microbiota in critically ill septic patients admitted to the intensive care unit (ICU). Methods: Forty critically ill patients diagnosed with sepsis were assessed in this pilot randomized controlled trial. Patients were randomized into two groups: Lactocare and control groups. Patients in the Lactocare group received two capsules of Lactocare® for 10 days. Fecal samples were taken from all patients on days 1 and 10 for determining the gut microbial pattern. The primary outcome was gut microbial flora, and secondary outcomes were intensive care unit (ICU) length of stay and mortality. Results: Intragroup changes showed that all microbial flora considerably changed during the study period; the number of microbial flora significantly decreased in the control group and increased in the Lactocare group. Patients in the Lactocare group had a significantly lower incidence of diarrhea and infection with multidrug-resistant organisms. There was no difference in ICU length of stay in the Lactocare group compared to the control group (p= 0.289). The mortality rate was 30% in the control group compared to 20% in the Lactocare group (p: 0.465). Conclusion: This study showed a remarkable effect of the probiotic preparation on the gut microbiota in critically ill septic patients as it decreased the number of opportunistic pathogens. However, additional clinical research is needed to translate research into clinical practice to refine the clinical indication of the specific probiotic strains.